The Portrait of Jasmine’s Behavior and Personality Structure in “Below Her Mouth” Movie - Priyoto, Priyoto; Mujani, Sahril; Lestari, Rini Dwi (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
The purpose of this study was to analyze the personality structure of Jasmine's behavior in Below Her Mouth movie. With this research, it is hoped that the adolescent generation, in particular, can be wiser and more selective in choosing associations and can limit things that can affect their lives in the future, especially from the environment and friendships. This research uses qualitative methods. The object used in this study is a film with a lesbian theme, namely the film Below Her Mouth. The data collected is obtained from the results of watching the film and sorting out the scenes and dialogues in the film. The results showed that Jasmine's behavior in the film Below Her Mouth is influenced by the personality structure dominated by the id structure, Jasmine's cause of eventually becoming a lesbian is influenced by internal and external factors where masculinity and seduction are part of external factors then sexual attraction and youth experiences are part of internal factors